(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
A new Stage, the Gelasian, is proposed as the third upper subdivision of the Pliocene Series. The GSSP of the base of the Gelasian Stage and of the Middle Pliocene-Upper Pliocene boundary is coincident with a "sapropel" level which outcrops in the Monte San Nicola section, near Gela (Southern Sicily, Italy). This level corresponds to the Mediterranean Precessional Related Sapropel 250 of Hilgen (1991)and has an astrochronological age of 2.589 Ma. It correspondes to the oxygen isotopic Stage 103 of Raymo et al.(1989) and in the boundary stratotype section it outcrops 1 meter above the Gauss-Matuyama paleomagnetic boundary. Astrochronologic, magnetostratigraphic, biostratigraphic and climatostratigraphic elements to approximate the GSSP of the Gelasian outside the stratorype section are presented.